2004
DOI: 10.1021/ic049433j
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Acceleration of Zirconium(IV)-Assisted Peptide Hydrolysis at Neutral pH

Abstract: 4,13-Diaza-18-crown-6 substantially increases the rate of zirconium(IV) hydrolysis of unactivated peptide amide bonds under near-physiological conditions of temperature and pH. In the presence of this azacrown ether, ZrCl(4) efficiently hydrolyses both neutral and negatively charged peptides (pH 7.0-7.3, 37-60 degrees C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 26 publications
1
75
0
Order By: Relevance
“…The acceleration factor ranges from 2.3 for Zr(IV)-substituted Lindqvist type polyoxymetalates (Zr(IV)-Ld POMs) to 36 for Ce(IV)-substituted Keggin type polyoxymetalates (Ce(IV)-Kg POMs) [18][19][20]23,24,[27][28][29]31,32]. For Ser-Gly the intermolecular attack of the hydroxyl group on the carbonyl carbon would require the formation of an unfavorable four-membered ring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The acceleration factor ranges from 2.3 for Zr(IV)-substituted Lindqvist type polyoxymetalates (Zr(IV)-Ld POMs) to 36 for Ce(IV)-substituted Keggin type polyoxymetalates (Ce(IV)-Kg POMs) [18][19][20]23,24,[27][28][29]31,32]. For Ser-Gly the intermolecular attack of the hydroxyl group on the carbonyl carbon would require the formation of an unfavorable four-membered ring.…”
Section: Discussionmentioning
confidence: 99%
“…Although the azacrown ether increased the Zr(IV) precipitation, the hydrolysis was accelerated. The application of Tris decreased the amount of Zr(IV) precipitate, but the hydrolysis rate also decreased [24].…”
Section: Poorly Soluble Metal Hydroxidesmentioning
confidence: 95%
See 2 more Smart Citations
“…Many metal ions and metal complexes are found to promote or catalyze the hydrolysis of peptide bonds in short peptides. [10][11][12][13][14][15] Bal's group identified the specific Ni(II)-related hydrolysis of peptide bonds preceding Ser/Thr-Xaa-His sequences. [16][17][18] In previous studies, the specific Cu(II)-related hydrolysis was demonstrated for peptide bonds preceding Ser-His and Thr-His sequences at elevated temperatures and pH values.…”
Section: Introductionmentioning
confidence: 99%